Cultural Intelligence and Gastronomy for Talent Sustainability in Regenerative Tourism: Evidence from Borobudur - Atmaja, Hanung Eka; Mafruhah, Izza; Widanti, Eki Melina; Nur, Sofyan Ashari; Syakira, Agustya; Alfareza, Dimas (Annals of Human Resource Management Research, 2026)
Purpose: This study examines the influence of cultural intelligence and local gastronomy on talent sustainability and analyzes their implications for regenerative tourism development in Borobudur heritage destinations. Research Methodology: A quantitative, cross-sectional survey was conducted among tourism stakeholders in Borobudur. Using proportional stratified random sampling, 320 valid responses were collected between May and July 2025. Data were analyzed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) with SmartPLS 4, including measurement model assessment and bootstrapping for hypothesis testing. Results: Cultural intelligence and local gastronomy significantly and positively influence talent sustainability. Talent sustainability strongly predicts regenerative tourism development and mediates the relationships between cultural intelligence, local gastronomy, and regenerative outcomes. The findings indicate that sustained human capability development is central to achieving restorative tourism practices. Conclusions: Human resource management strategies grounded in cultural competence and gastronomy-based local identity enhance talent retention and support the transition from sustainable to regenerative tourism. Limitations: This study is limited to a single heritage destination and relies on cross-sectional, self-reported data, which may constrain generalizability and introduce potential common method bias. Contributions: This research provides an integrated empirical model linking cultural intelligence, gastronomy, sustainable HRM, and regenerative tourism within a UNESCO heritage context.